Redesign of Innovative and Ergonomic College Chair to Improve Student Performance - Soewardi, Hartomo; Arum Dindadhika, Ken (International Journal of Engineering and Technology, 2018)
Poor sitting and an inconvenient change of sitting position during teaching and learning process will inflict the musculoskeletal disorder on several parts of the body beside it may produce some problems for students. One of the problems is decrement of concentration level in apprehending course materials. It can negatively affect student performance. Thus, it is necessary to improve learning, facilities, especially in the form of an innovative chair to accommodate the studentâ€™s need. This paper presents a study to redesign college chair to be more innovative and ergonomics in order to meet studentâ€™s requirement. Kansei Engineering (KE) method was used to determine the engineering specification of design with mapping process from studentâ€™s Kansei. Anthropometry data was also used to support the design. Statistical analysis was conducted to test the hypothesis. The result of this study showed that a new innovative and ergonomic design of chair was proven to be valid to meet user's need at 5 % of significance level.Â Â